Dendritic spine dynamics – a key role for kalirin-7 - Penzes, Peter (2008)
Changes in the structure and function of dendritic spines contribute to numerous physiological processes such as synaptic transmission and plasticity, as well as behavior, including learning and memory. Moreover, altered dendritic spine morphogenesis and plasticity is an endophenotype of many neurodevelopmental and neuropsychiatric disorders. Hence, the molecular mechanisms that control spine plasticity and pathology have been under intense investigation over the past few years. A series of recent studies has improved our understanding of spine dynamics by establishing kalirin-7 as an important regulator of dendritic spine development as well as structural and functional plasticity, providing a model for the molecular control of structural plasticity and implicating kalirin-7 in synaptic pathology in several disorders including schizophrenia and Alzheimer’s disease.